Strategies for CRISPR/Cas9-mediated genome editing: from delivery to production of modified plants - Gordon-Kamm, William (Burleigh Dodds Series in Agricultural Science, 2021)
Despite the conspicuous and rapid development of genome editing tools, implementing this technology in plants often remains constrained by our inability to regenerate fertile genome-modified plants. Finding a viable combination of delivery method, genome editing reagents, and plant regeneration system has often been both crop-specific and crop-limited. Recent progress using morphogenic genes such as Wuschel2 (Wus2) and Babyboom (Bbm) has alleviated some of these crop-specific challenges, and along with other improvements, continues to expand the range of plants that can be edited.